Analisis Peningkatan Kapasitas Usaha Ikm Kain Tapis Lampung Studi Kasus Lagawifest 2022 - Kusmulyono, Muhammad Setiawan; Agustiawan, Sonny; Setiawati, Isti Budhi; Putra, Antasari; Sulistya, Dickie (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Tapis Lampung is one of the wealth of the archipelago's fabric which has great potential as a source of creative economic commodities in Lampung Province. Unfortunately, its popularity is inferior to batik, ulos, songket, and other wastra. The Bangga Buatan Indonesia Lagawifest 2022 program which was held in Lampung Province then succeeded in curating 8 selected Lampung Tapis IKMs (small medium industry) to then be encouraged to become IKM representatives who can improve product quality and business performance. Through a qualitative approach with the FGD technique, it was found that the biggest problems of the Lampung Tapis IKM who were the resource persons were digital marketing problems, limited production assets, weak design capabilities, limited production assets, and several other problems. Through the assistance of the 2022 BBI Program, each IKM is given guidance and directed to develop themselves through programs that will be carried out by the government, namely technical guidance on digital marketing, design, branding, business finance, and business meetings.